Transposons play an important role in the evolution and diversification of centromeres among closely related species - Gao, Dongying; Jiang, Ning; Wing, Rod A.; Jiang, Jiming; Jackson, Scott A. (Frontiers in Plant Science, 2015)
Centromeres are important chromosomal regions necessary for eukaryotic cell segregation and replication. Due to high amounts of tandem repeats and transposons, centromeres have been difficult to sequence in most multicellular organisms, thus their sequence structure and evolution are poorly understood. In this study, we analyzed transposons in the centromere 8 (Cen8) from the African cultivated rice (O. glaberrima) and two subspecies of the Asian cultivated rice (O. sativa), indica and japonica. We detected much higher transposon contents (>69%) in centromere regions than in the whole genomes of O. sativa ssp. japonica and O. glaberrima (~35%). We compared the three Cen8s and identified numerous recent insertions of transposons that were frequently organized into multiple-layer nested blocks, similar to nested transposons in maize. Except for the Hopi retrotransposon, all LTR retrotransposons were shared but exhibit different abundances amongst the three Cen8s. Even though a majority of the transposons were located in intergenic regions, some gene-related transposons were found and may be involved in gene diversification. Chromatin immunoprecipitated (ChIP) data analysis revealed that 165 families from both Class I and Class II transposons were found in CENH3-associated chromatin sequences. These results indicate essential roles for transposons in centromeres and that the rapid divergence of the Cen8 sequences between the two cultivated rice species was primarily caused by recent transposon insertions.